PERSEPSI TOKOH AGAMA DAN PEMANGKU ADAT DI NAGARI LUBUK BASUNG KABUPATEN AGAM DALAM MENGGUNAKAN JASA DAN PRODUK BANK SYARIAH - Rahmi Detya Ditri; Andis Febrian (Adisam Publisher, 2024)
The background to this research is that in Lubuk Basung, there are conventional banks and sharia banks as financial institutions that are equally trusted. Given that the sharia label is associated with the latter, this presents a promising opportunity for Islamic banking to gain support from religious leaders. Some individuals may be hesitant to utilize Islamic banking services due to the perception that Islamic banks operate based on their own principles or beliefs. A community figure is someone who is considered influential in the surrounding community, including the community figure here, namely Walinagari Lubuk Basung, who is considered an elder or a person with authority. The type of research that the author conducted was field research which was descriptive qualitative in nature. Data collection techniques are carried out through observation and interviews with religious and community leaders to ensure the general public's evaluation or understanding of Sharia banks. Based on the results of research and data analysis that has been carried out in Nagari Lubuk Basung, it is concluded that the perception of religious leaders in Nagari Lubuk Basung towards sharia banks is quite good. They already know that sharia banks are banks that are run on the basis of religious rules, where the bank does not apply an interest system. , unlike conventional banks which apply an interest system. The perception of traditional stakeholders towards the Nagari Lubuk Basung sharia bank has poor understanding and knowledge, compared to the perception of their religious leaders. There are those who only know but don't use Sharia banks.